2011
DOI: 10.3389/fpsyg.2011.00324
|View full text |Cite
|
Sign up to set email alerts
|

Bilingualism and Inhibitory Control Influence Statistical Learning of Novel Word Forms

Abstract: We examined the influence of bilingual experience and inhibitory control on the ability to learn a novel language. Using a statistical learning paradigm, participants learned words in two novel languages that were based on the International Morse Code. First, participants listened to a continuous stream of words in a Morse code language to test their ability to segment words from continuous speech. Since Morse code does not overlap in form with natural languages, interference from known languages was minimized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
121
7
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(133 citation statements)
references
References 60 publications
4
121
7
1
Order By: Relevance
“…Another limitation of the current evidence is that previous studies have considered the role of attention and working memory in bilingual novel-word learning separately (e.g., Bartolotti et al 2011;Papagno & Vallar, 1995). We are not aware of studies that have examined the roles of attentional control and working memory mechanisms simultaneously in learning novel-words in bilinguals.…”
Section: Role Of Working Memory In Executive Control and Word Learningmentioning
confidence: 54%
See 2 more Smart Citations
“…Another limitation of the current evidence is that previous studies have considered the role of attention and working memory in bilingual novel-word learning separately (e.g., Bartolotti et al 2011;Papagno & Vallar, 1995). We are not aware of studies that have examined the roles of attentional control and working memory mechanisms simultaneously in learning novel-words in bilinguals.…”
Section: Role Of Working Memory In Executive Control and Word Learningmentioning
confidence: 54%
“…However, in a recent study Kaushanskaya (2012) found that bilinguals outperformed monolinguals in novel-word learning even when their verbal short-term memory ability was matched challenging the view that the novel-word learning advantage was attributed to enhanced verbal short-term memory. Instead, Kaushanskaya argued that the advantage was due to the impact of the bilingual experience on learning (see also Bartolotti et al, 2011;Kaushanskaya & Marian, 2009a, b).…”
Section: Role Of Working Memory In Executive Control and Word Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, language learners must walk a fine line between allowing co-activation of their languages for integration and transfer, and inhibiting previous languages to allow novel learning and processing. Consistently, evidence from a number of studies with younger adults suggests that cognitive resources are recruited to manage interference from non-target languages in individuals who are learning a novel language (e.g., Raboyeau et al, 2010;Bartolotti et al, 2011).…”
mentioning
confidence: 78%
“…Instead of age, composite scores of digit span and orientation were found to predict English verbal fluency in the reference group as well as short-term maintenance of knowledge in the SPECSS learners. Verbal short-term memory (e.g., Papagno and Vallar, 1995;Kaushanskaya et al, 2011) and attention skills (e.g., Bartolotti et al, 2011) have been linked to the ability to acquire novel vocabulary and process an L2. It is thus consistent with previous findings that individuals with higher scores on digit span/orientation subtests were more successful at learning English independently prior to our SPECSS curriculum, and that the learners who participated in our SPECSS curriculum better maintained skills across the curriculum.…”
Section: Cognitive Factors In Older Adults' Ability To Maintain and Lmentioning
confidence: 99%